1989
DOI: 10.1182/blood.v73.1.214.214
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel form of transferrin receptor preferentially expressed on normal erythroid progenitors and precursors

Abstract: A panel of monoclonal antibodies (MoAbs) against cell surface proteins of early BFUe progeny was characterized. Five of these antibodies (Abs) reacted with normal erythroid, but not myeloid, bone marrow cells. Each of the five antibodies, typified by Ab 69.20, immunoprecipitated a dimeric complex of 185,000, which is composed of two identical disulfide-bonded subunits. This antigen had affinity for transferrin, and was essentially identical in biochemical characteristics to transferrin receptors precipitated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…The fact that high levels of glycophorin A (recognized by the CD235a antibody) (Robinson et al, 1981) and of the transferrin receptor I (recognized by CD71) (Iacopetta et al, 1982; Sawyer and Krantz, 1986) expression also occur during the maturation of human erythroblasts has inspired a citofluorimetric definition of human cells according to the same principle used for the mouse (Wojda et al, 2003). However, in humans the increased iron requirement associated with the progression of erythroid maturation is met not only by increasing the expression of the transferrin receptor I, but also by activating the expression of an erythroid‐specific receptor isoform (Cotner et al, 1989) encoded by the transferrin receptor 2 gene (Kawabata et al, 1999). Preliminary experiments had indicated that erythroid differentiation was associated with a pattern of CD71 expression similar to that observed in the mouse in only 40% of the donor population to whom we had access (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The fact that high levels of glycophorin A (recognized by the CD235a antibody) (Robinson et al, 1981) and of the transferrin receptor I (recognized by CD71) (Iacopetta et al, 1982; Sawyer and Krantz, 1986) expression also occur during the maturation of human erythroblasts has inspired a citofluorimetric definition of human cells according to the same principle used for the mouse (Wojda et al, 2003). However, in humans the increased iron requirement associated with the progression of erythroid maturation is met not only by increasing the expression of the transferrin receptor I, but also by activating the expression of an erythroid‐specific receptor isoform (Cotner et al, 1989) encoded by the transferrin receptor 2 gene (Kawabata et al, 1999). Preliminary experiments had indicated that erythroid differentiation was associated with a pattern of CD71 expression similar to that observed in the mouse in only 40% of the donor population to whom we had access (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…It is now clear that the intracellular processing of transferrin to effect iron release involves more than one pathway, as demonstrated by kinetic studies [12,52] and by the effect of toxins [53-551. The number (more than one, but how many more is not clear) and the functional significance of the separate pathways and whether they involve the receptor [56], the handling of iron in the endocytic vesicle, or its transit through the cytosol and uptake by mitochondria--or some combination of these-remains to be elucidated. A diagram summarizing the classic scheme and some of the changes that need to be included in a revised scheme is shown in Figure 1.…”
Section: A Revised Formulationmentioning
confidence: 99%
“…Ένα χαρακτηριστικό των προγονικών κυττάρων μόνο της ερυθράς σειράς είναι η εν αφθονία παρουσία υποδοχέων τρανσφαιρίνης που είναι απαραίτητοι για τη μεταφορά σιδήρου και τη σύνθεση της αιμοσφαιρίνης. Η μέγιστη έκφραση των υποδοχέων αυτών απαντά στο στάδιο των CFU-E και των προδρόμων κυττάρων της ερυθράς σειράς (προερυθροβλαστών), ενώ στα δικτυοερυθροκύτταρα ανευρίσκονται σε μικρότερο βαθμό (Cotner 1989, Sawyer 1996, Ponka 1997…”
Section: αλληλουχια των γεγονοτων της ερυθρο-ποιησηςunclassified